Dokumentasi Referensi Folklor Lisan di Negeri Rutong, Kecamatan Leitimur Selatan, Maluku - Wuarlela, Mouren; Marantika, Meyke; Apalem, Delvia R.; Hiariej, Chrisanty (Universitas Pattimura, 2025)
Verbal folklore reference documentation is one of the efforts to sustain and preserve oral folklore through the process of collecting, selecting, processing and storing in written descriptions. This study aims to describe the form and function of oral folklore in Negeri Rutong , South Leitimur District, Maluku. The research method used is a qualitative research method. The techniques used are observation and interview techniques to collect oral folklore data. The research results obtained include nicknames such as Talahattu Galoba; naming places such as Batu Minom Aer; traditional expressions such as ale makang isi, beta anana bone jua; traditional questions such as cigulu-cigulu satu, bu bale bu bale Bulan tabala, apakah itu?; Gandong Amalopu (Amakele Lopurisa) rhyme